The Concept of Dressing in the Perspective of the Hadith - Dwi Rizki Mulyani; Muhammad Nuh Siregar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to reveal the concept of dressing properly and correctly according to Islamic law. The method used in this research is literature study. From this research, it can be concluded that the application of good and proper dressing includes the obligation to cover the aurat, avoid thin and tight clothes, not wearing the clothes of the opposite sex, and the prohibition for men to wear clothes longer than the ankles (isbal). In addition, clothing with images of crosses or haram living creatures, should not resemble non-Muslim clothing, and not for the purpose of seeking popularity. For men, wearing silk and gold clothing is also prohibited. Women are required to refrain from displaying jewelry (tabarruj), are advised to start dressing from the right side, and are encouraged to recite prayers when putting on new clothes.